An efficient regeneration system through in vitro somatic embryogenesis of barley (Hordeum vulgare L.) - Haque, M; Islam, SMS (Journal of Bio-Science, 2019)
This study was carried out to improve an efficient protocol for in vitro callus induction and plant regeneration using Bangladeshi barley genotypes collected from BARI, Gazipur, Bangladesh. After sterilization embryos were separated carefully from mature seeds of six barley genotypes (BB-1, BB-2, BB-3, BB-4, BB-5 and BB-6) and cultured them in MS medium supplemented with various concentration and combination of PGRs for callus induction and regeneration. Out of six genotypes BB-6 showed highest (38.17%) callus induction in MS + 4.0 mg/l 2,4-D + 200 mg/l L-proline + 300 mg/l casein hydrolysate; whereas, BB-4 and BB-5 showed no callus induction in the same medium. For plant regeneration from embryogenic calli the same genotype (BB-6) also performed the best results (19.25%) in MS medium supplemented with 1.5 mg/l BAP + 30 g/l sucrose. Analysis of variance (ANOVA) showed highly significant differences among the media and the genotypes. J. bio-sci. 27: 89-99, 2019